Co3O4-alpha-MnO2 material as well as preparation method and application thereof
By modifying Co3O4 on the surface of rod-shaped α-MnO2 material and uniformly dispersing Co elements with urea, Co3O4@α-MnO2 material was prepared, which solved the problem of poor catalytic chlorobenzene activity and CO2 yield in the high-temperature stage of the existing MnO2 catalyst, achieving higher catalytic activity and CO2 yield, and improving the durability and anti-interference ability of the material.
Patent Information
- Application Number
- CN202411799404.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing MnO2 catalysts have poor catalytic activity and CO2 yield in the catalytic oxidation process of chlorobenzene, especially in the high-temperature stages.
Co3O4@α-MnO2 material was prepared by modifying Co3O4 on the surface of the rod-shaped α-MnO2 material and evenly dispersing Co elements using urea in the hydrothermal reaction.
The catalytic activity and CO2 yield of the material during the catalytic oxidation of chlorobenzene in the high-temperature stage were improved, and the degree of inactivation of the material was reduced, thereby enhancing the tolerance and anti-interference of the actual industrial flue gas components.
Smart Images

Figure CN119608178A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst preparation and air pollution control, and specifically relates to a Co3O4@α-MnO2 material and a preparation method and application thereof. Background Art
[0002] The emission of VOCs is extremely harmful to human health and the ecological environment. On the one hand, VOCs are highly irritating and can cause irreversible damage to the respiratory system and central nervous system when inhaled by the human body. On the other hand, VOCs can also seriously affect the atmospheric environment. Most VOCs are highly photochemically reactive and easily react with NO. x Reacts to form ozone or adheres to fine particulate matter PM 2.5 Chlorinated volatile organic compounds (CVOCs) are PM 2.5 It is an important precursor for the formation of VOCs and O3. Due to its high toxicity, high stability and difficulty in degradation, it has become the focus of attention in the field of VOCs control.
[0003] Among the many treatment technologies for CVOCs, catalytic oxidation technology is considered to be a promising end-of-pipe treatment technology that is very suitable for industrial applications. The core of catalytic oxidation technology lies in the selection of catalysts. Although the catalytic activity of transition metals is inferior to that of precious metals, they are widely used in the field of catalysis due to their low price, high resistance to chlorine poisoning, and good high-temperature thermal stability. 2+ / Mn 3+ / Mn 4+ It is favored by researchers due to its redox cycle, high reserves on Earth, low cost and non-toxicity, and is widely used in the catalytic oxidation of CVOCs. It is reported that the redox cycle between the multivalent states of manganese can produce oxygen vacancies, thereby promoting the adsorption and activation of oxygen, and producing abundant oxygen species for the oxidation of CVOCs.
[0004] Mn elements with various valence states can present various crystal structures (such as MnO2, Mn2O3, Mn3O4, etc.), and these different crystal structures have different catalytic oxidation performances for CVOCs. It is worth noting that MnO2 calcined in the medium-high temperature range has excellent oxygen species mobility among various MnO x However, MnO2 has some defects and shortcomings, such as poor catalytic activity for chlorobenzene, low CO2 yield, especially poor catalytic activity and CO2 yield in the high temperature section, and poor actual industrial application ability. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the present invention provides a Co3O4@α-MnO2 material and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for preparing Co3O4@α-MnO2 material comprises the following steps:
[0008] (1) KMnO4 and (NH4)2C2O4·H2O are added to water for ultrasonic dispersion, followed by hydrothermal reaction, and finally filtered, washed, dried, and calcined to obtain rod-shaped α-MnO2 material;
[0009] (2) Rod-shaped α-MnO2 material, Co(NO3)2·6H2O and urea are placed in water, followed by hydrothermal reaction, and finally filtered, washed, dried and calcined to obtain Co3O4@α-MnO2 material.
[0010] The present invention uses urea to evenly disperse the Co element on the surface of the rod-shaped α-MnO2 material, and can also improve the material's catalytic activity and CO2 yield in the catalytic oxidation of chlorobenzene. If urea is lacking, the chlorobenzene conversion rate and CO2 yield of the Co3O4@α-MnO2 material at 350°C are significantly reduced, and the stability of the catalytic oxidation of chlorobenzene is also reduced.
[0011] As a preferred embodiment of the present invention, the mass ratio or molar ratio of KMnO4 and (NH4)2C2O4·H2O is 2:1.
[0012] As a preferred embodiment of the present invention, in step (1), the temperature of the hydrothermal reaction is 180° C. and the time is 24 hours.
[0013] As a preferred embodiment of the present invention, in the step (1), the calcination atmosphere is an air atmosphere, the calcination temperature is 400° C., and the calcination time is 4 hours.
[0014] The present invention adopts the above hydrothermal temperature, time and calcination temperature and time to obtain rod-shaped α-MnO2 material. If the hydrothermal and calcination parameters are not within the specified range of the present invention, rod-shaped α-MnO2 material cannot be generated, and the chlorobenzene conversion rate and CO2 yield of the composite material at 350°C are not significantly improved.
[0015] As a preferred embodiment of the present invention, the mass ratio of the rod-shaped α-MnO2 material to Co(NO3)2·6H2O is 1:0.025-0.5; the molar ratio of Co(NO3)2·6H2O to urea is 1:10.
[0016] As a preferred embodiment of the present invention, in step (2), the temperature of the hydrothermal reaction is 120° C. and the time is 12 h.
[0017] As a preferred embodiment of the present invention, in the step (2), the calcination atmosphere is air atmosphere, the heating rate is 2°C / min, the calcination temperature is 400°C, and the calcination time is 4h.
[0018] The Co3O4@α-MnO2 material is prepared by the preparation method of the Co3O4@α-MnO2 material of the present invention.
[0019] As a preferred embodiment of the present invention, the Co3O4@α-MnO2 material is Co3O4 loaded on the surface of a rod-shaped α-MnO2 material.
[0020] As a preferred embodiment of the present invention, the Co3O4@α-MnO2 material is used in the catalytic oxidation of chlorobenzene.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: the surface modification of the rod-shaped α-MnO2 material with Co3O4 improves the material's catalytic activity and CO2 yield in the high-temperature catalytic oxidation of chlorobenzene (an increase of 34% compared with the original α-MnO2), the degree of deactivation in continuous experiments is also greatly reduced, and it shows higher tolerance and anti-interference to actual industrial flue gas components such as SO2, NO and toluene, thereby improving its potential for actual industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 These are scanning electron microscope (SEM) images of the α-MnO2 and 1Co@α-MnO2 samples of the present invention; (a) is the α-MnO2 material prepared in Comparative Example 1; (b) is the 1Co@α-MnO2 sample prepared in Example 3.
[0023] Figure 2 The catalytic activity of the samples prepared in Examples 1-4 of the present invention and Comparative Example 1 to chlorobenzene and the CO2 yield graph; wherein (a) is the catalytic activity graph of chlorobenzene; and (b) is the CO2 yield graph.
[0024] Figure 3 This is a durability test diagram of the samples prepared in Comparative Example 1 and Example 3 of the present invention.
[0025] Figure 4 These are durability test graphs of the samples prepared in comparative example 1 and example 3 of the present invention after the coexisting components are introduced; (a) is a durability test graph after the introduction of SO2; (b) is a durability test graph after the introduction of NO; (c) is a durability test graph after the introduction of toluene.
[0026] Figure 5 This is the activity diagram of the samples prepared in Comparative Examples 2-4 of the present invention for catalytic oxidation of chlorobenzene. DETAILED DESCRIPTION
[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0028] Example 1
[0029] A method for preparing Co3O4@α-MnO2 material comprises the following steps:
[0030] (1) Weigh 3.16 g KMnO4 and 1.42 g (NH4)2C2O4·H2O and add them to 70 mL deionized water. Ultrasonic dispersion is performed for 20 min to fully dissolve and mix to obtain a purple mixed solution.
[0031] (2) The purple solution was transferred to a high pressure reactor and subjected to a hydrothermal reaction at 180 °C for 24 h.
[0032] (3) After cooling, the precipitate was filtered, washed with deionized water for 3-5 times, and dried in an oven at 80°C for 12-14 hours.
[0033] (4) The dried sample was ground and placed in a tube furnace under air atmosphere and heated to 400°C at a heating rate of 2°C / min and maintained for 4 h for calcination to obtain a rod-shaped α-MnO2 carrier.
[0034] (5) Weigh 1 g of α-MnO2 carrier, 0.05 g of Co(NO3)2·6H2O and 0.1 g of urea (the molar ratio of Co(NO3)2·6H2O to urea is 1:10), dissolve them in 70 mL of deionized water, and ultrasonically disperse them for 20-30 min until they are uniform to obtain a mixed solution.
[0035] (6) The mixed solution was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120 °C for 12 h. After cooling to room temperature, the resulting precipitate was filtered with deionized water, washed 3-5 times, and dried in an oven at 80 °C for 12-14 h. The mixture was then heated to 400 °C at a heating rate of 2 °C / min in an air atmosphere and calcined for 4 h to obtain a rod-shaped α-MnO2 material modified with Co3O4 on the surface, which was recorded as 0.5Co@α-MnO2.
[0036] Example 2
[0037] The only difference between the preparation method of a Co3O4@α-MnO2 material and Example 1 is that in step (5), the mass of Co(NO3)2·6H2O is 0.1 g, and the mass of urea is 0.2 g. The finally obtained Co3O4@α-MnO2 material is marked as 1Co@α-MnO2.
[0038] like Figure 1As shown in b, the synthesized 1Co@α-MnO2 sample still exhibits a good rod-like morphology, indicating that the loading of Co3O4 does not change the morphology of the original α-MnO2.
[0039] Example 3
[0040] The only difference between the preparation method of Co3O4@α-MnO2 material and Example 1 is that in step (5), the mass of Co(NO3)2·6H2O is 0.5 g, and the mass of urea is 1.0 g. The finally obtained Co3O4@α-MnO2 material is marked as 5Co@α-MnO2.
[0041] The synthesized 5Co@α-MnO2 sample still exhibits a good rod-like morphology, indicating that the loading of Co3O4 does not change the morphology of the original α-MnO2.
[0042] Example 4
[0043] The only difference between the preparation method of Co3O4@α-MnO2 material and Example 1 is that in step (5), the mass of Co(NO3)2·6H2O is 1.0 g, and the mass of urea is 2.0 g. The finally obtained Co3O4@α-MnO2 material is marked as 10Co@α-MnO2.
[0044] The synthesized 10Co@α-MnO2 sample still exhibits a good rod-like morphology, indicating that the loading of Co3O4 does not change the morphology of the original α-MnO2.
[0045] Comparative Example 1
[0046] A method for preparing an α-MnO2 material comprises the following steps:
[0047] (1) Weigh 3.16 g KMnO4 and 1.42 g (NH4)2C2O4·H2O and add them to 70 mL deionized water. Ultrasonic dispersion is performed for 20-30 min to fully dissolve and mix to obtain a purple mixed solution.
[0048] (2) The purple solution was transferred to a high pressure reactor and subjected to a hydrothermal reaction at 180 °C for 24 h.
[0049] (3) After cooling, the precipitate was filtered, washed with deionized water for 3-5 times, and dried in an oven at 80°C for 12-14 hours.
[0050] (4) The dried sample was ground and placed in a tube furnace in an air atmosphere and heated to 400°C at a heating rate of 2°C@min and maintained for 4 h for calcination to obtain rod-shaped α-MnO2. The scanning electron microscope image is shown in Figure 2. Figure 1As shown in a, the synthesized rod-shaped α-MnO2 sample exhibits a good rod-like morphology.
[0051] Comparative Example 2
[0052] A method for preparing a Co3O4 / α-MnO2 material comprises the following steps:
[0053] (1) Weigh 3.16 g KMnO4 and 1.42 g (NH4)2C2O4·H2O and add them to 70 mL deionized water. Ultrasonic dispersion is performed for 20 min to fully dissolve and mix to obtain a purple mixed solution.
[0054] (2) The purple solution was transferred to a high pressure reactor and subjected to a hydrothermal reaction at 180 °C for 24 h.
[0055] (3) After cooling, the precipitate was filtered, washed with deionized water for 3-5 times, and dried in an oven at 80°C for 12-14 hours.
[0056] (4) The dried sample was ground and placed in a tube furnace under air atmosphere and heated to 400°C at a heating rate of 2°C / min and maintained for 4 h for calcination to obtain a rod-shaped α-MnO2 carrier.
[0057] (5) Weigh 0.1 g of Co(NO3)2·6H2O and dissolve it in 9.5 ml of deionized water. Ultrasonic dispersion is performed for 20-30 min to fully dissolve and mix to obtain a light red solution.
[0058] (6) Weigh 1 g of α-MnO2 carrier into a beaker, drop the light red solution evenly into the beaker, and disperse it by ultrasonic for 20-30 min. After standing overnight, place the solution in an oven at 80 °C and dry for 12-14 h.
[0059] (7) The dried sample was ground and placed in a tubular furnace in an air atmosphere and heated to 400°C at a heating rate of 2°C / min and maintained for 4 hours for calcination to obtain Co3O4 surface-modified α-MnO2 prepared by an equal volume impregnation method, denoted as 1Co / α-MnO2, indicating that the mass fraction of Co3O4 on the Co3O4 surface-modified α-MnO2 catalyst prepared in this comparative example is 1%.
[0060] Comparative Example 3
[0061] The only difference between the preparation method of the Co3O4 / α-MnO2 material in this comparative example and that in comparative example 2 is that in step (5), the mass of Co(NO3)2·6H2O is 0.5 g. The final obtained Co3O4 / α-MnO2 material is marked as 5Co / α-MnO2, indicating that the mass fraction of Co3O4 on the α-MnO2 catalyst modified with the Co3O4 surface prepared in this comparative example is 5%.
[0062] Comparative Example 4
[0063] The only difference between the preparation method of the Co3O4 / α-MnO2 material in this comparative example and that in comparative example 2 is that in step (5), the mass of Co(NO3)2·6H2O is 1.0 g. The final obtained Co3O4 / α-MnO2 material is marked as 10Co / α-MnO2, indicating that the mass fraction of Co3O4 on the α-MnO2 catalyst modified with the Co3O4 surface prepared in this comparative example is 10%.
[0064] Comparative Example 5
[0065] A method for preparing Co3O4@α-MnO2 material comprises the following steps:
[0066] (1) Weigh 6.99 g of MnSO4·H2O and 4.36 g of KMnO4 and dissolve them in 50 mL of deionized water.
[0067] (2) The above two solutions were evenly added into 50 mL of deionized water and stirred in a 60 °C water bath for 2 h.
[0068] (3) The above solution was filtered and washed until neutral to obtain a precipitate, and the precipitate was dried at 80° C. for 12 h.
[0069] (4) The dried sample was ground and placed in a tube furnace under air atmosphere and heated to 400 °C at a heating rate of 2 °C / min and maintained for 12 h for calcination to obtain spherical α-MnO2.
[0070] (5) Weigh 1 g of spherical α-MnO2 carrier, 0.05 g of Co(NO3)2·6H2O and 0.1 g of urea (the molar ratio of Co(NO3)2·6H2O to urea is 1:10), dissolve them in 70 mL of deionized water, and ultrasonically disperse them for 20-30 min until they are uniform to obtain a mixed solution.
[0071] (6) The mixed solution was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120°C for 12 h. After cooling to room temperature, the resulting precipitate was filtered with deionized water, washed 3-5 times, and dried in an oven at 80°C for 12-14 h. The mixture was then heated to 400°C at a heating rate of 2°C / min in an air atmosphere and calcined for 4 h to obtain a rod-shaped α-MnO2 material modified with Co3O4.
[0072] Comparative Example 6
[0073] A method for preparing Co3O4@α-MnO2 material comprises the following steps:
[0074] (1) Weigh 1.69 g of MnSO4·H2O and 3.95 g of KMnO4 and dissolve them in 80 mL of deionized water.
[0075] (2) The above solution was transferred to a high pressure reactor and subjected to a hydrothermal reaction at 100 °C for 12 h.
[0076] (3) After cooling to room temperature, the resulting precipitate was filtered, washed 3-5 times with deionized water, and then dried in an oven at 100°C for 12 h.
[0077] (4) The temperature was raised to 500 °C at a heating rate of 2 °C / min in an air atmosphere and calcined for 6 h to obtain flower-like α-MnO2.
[0078] (5) Weigh 1 g of flower-shaped α-MnO2 carrier, 0.05 g of Co(NO3)2·6H2O and 0.1 g of urea (the molar ratio of Co(NO3)2·6H2O to urea is 1:10), dissolve them in 70 mL of deionized water, and ultrasonically disperse them for 20-30 min until they are uniform to obtain a mixed solution.
[0079] (6) The mixed solution was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120°C for 12 h. After cooling to room temperature, the resulting precipitate was filtered with deionized water, washed 3-5 times, and dried in an oven at 80°C for 12-14 h. The mixture was then heated to 400°C at a heating rate of 2°C / min in an air atmosphere and calcined for 4 h to obtain a rod-shaped α-MnO2 material modified with Co3O4.
[0080] Comparative Example 7
[0081] A method for preparing Co3O4@δ-MnO2 material comprises the following steps:
[0082] (1) Weigh 1.35 g KMnO4 and 1.0 mL HCl (37 wt%) and dissolve them in 120 mL deionized water.
[0083] (2) The above solution was transferred to a high pressure reactor and subjected to a hydrothermal reaction at 120°C for 12 h.
[0084] (3) After cooling to room temperature, the obtained precipitate was filtered and washed 3-5 times with deionized water and ethanol, and then dried in an oven at 120°C for 12 h.
[0085] (4) In an air atmosphere, the temperature was raised to 80 °C at a heating rate of 2 °C / min and calcined for 12 h to obtain δ-MnO2.
[0086] (5) Weigh 1 g of δ-MnO2 carrier, 0.05 g of Co(NO3)2·6H2O and 0.1 g of urea (the molar ratio of Co(NO3)2·6H2O to urea is 1:10), dissolve them in 70 mL of deionized water, and ultrasonically disperse them for 20-30 min until they are uniform to obtain a mixed solution.
[0087] (6) The mixed solution was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120°C for 12 h. After cooling to room temperature, the resulting precipitate was filtered and washed 3-5 times with deionized water, and then dried in an oven at 80°C for 12-14 h. The temperature was then increased to 400°C at a heating rate of 2°C / min in an air atmosphere and calcined for 4 h to obtain a Co3O4 surface-modified δ-MnO2 material.
[0088] Comparative Example 8
[0089] A method for preparing Co3O4@γ-MnO2 material comprises the following steps:
[0090] (1) Weigh 6.32 g of MnSO4 and 8.56 g of (NH4)2S2O8 and dissolve them in 150 mL of deionized water.
[0091] (2) The above solution was transferred to a high pressure reactor and subjected to a hydrothermal reaction at 90°C for 24 h.
[0092] (3) After cooling to room temperature, the obtained precipitate was filtered and washed 3-5 times with deionized water and ethanol, and then dried in an oven at 120°C for 12 h.
[0093] (4) In an air atmosphere, the temperature was increased to 80°C at a heating rate of 2°C / min and calcined for 12 h to obtain γ-MnO2.
[0094] (5) Weigh 1 g of γ-MnO2 carrier, 0.05 g of Co(NO3)2·6H2O and 0.1 g of urea (the molar ratio of Co(NO3)2·6H2O to urea is 1:10), dissolve them in 70 mL of deionized water, and ultrasonically disperse them for 20-30 min until they are uniform to obtain a mixed solution.
[0095] (6) The mixed solution was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 120°C for 12 h. After cooling to room temperature, the resulting precipitate was filtered and washed 3-5 times with deionized water, and then dried in an oven at 80°C for 12-14 h. The temperature was then increased to 400°C at a heating rate of 2°C / min in an air atmosphere and calcined for 4 h to obtain a Co3O4 surface-modified γ-MnO2 material.
[0096] Effect example
[0097] (1) A certain mass of catalyst was used to evaluate the catalytic oxidation activity of chlorobenzene in a fixed bed reactor. The catalyst evaluation conditions were as follows:
[0098] The atmosphere conditions for simulating catalytic oxidation of chlorobenzene are: 600ppm chlorobenzene, 10% O2, N2 balance gas, gas flow rate = 100mL / min, corresponding reaction space velocity WHSV = 30000mL / (g·h), temperature 100-450, and chlorobenzene concentration and CO2 concentration are tested every 50℃. The chlorobenzene conversion rate and CO2 yield are calculated using the chlorobenzene concentration and CO2 concentration measured before and after the reaction. The results are shown in Tables 1 and Figure 2 .
[0099] (2) A certain mass of catalyst was subjected to continuous chlorobenzene catalytic oxidation activity evaluation in a fixed bed reactor. The catalyst evaluation conditions were as follows:
[0100] The atmosphere conditions for simulating catalytic oxidation of chlorobenzene are: 600ppm chlorobenzene, 10% O2, N2 balance gas, gas flow rate = 100mL / min, corresponding reaction space velocity WHSV = 30000mL / (g·h), temperature is 350℃, and time is 18h. The difference in chlorobenzene conversion rate at the beginning of the reaction and after 18 hours is used as the decrease in chlorobenzene degradation rate in 18 hours. The results are shown in Figure 3 .
[0101] Table 1
[0102]
[0103] according to Figure 2 It can be seen that the α-MnO2 prepared in Comparative Example 1 has high activity in the low temperature range of about 250°C, but is easily deactivated, and the CO2 yield is also relatively low. The samples prepared in Examples 1-4 have improved high-temperature catalytic activity for chlorobenzene, and the CO2 yield is also greatly improved, and 1Co@α-MnO2 exhibits the best catalytic activity in the high temperature range, and the CO2 yield is increased by 34% compared with the α-MnO2 prepared in Comparative Example 1. Figure 5 As shown in Table 1, compared with the α-MnO2 prepared in Comparative Example 1, the catalytic activity of the materials prepared in Comparative Examples 2-4 on chlorobenzene was not significantly improved, and even decreased, but the CO2 yield was improved. Figure 3 The activity of the α-MnO2 sample prepared in Comparative Example 1 in the durability test has been decreasing (the activity decreased by 14% in the 18h test), and the durability is poor. And according to Table 1 and Figure 3 It can be seen that the chlorobenzene conversion rate of the samples prepared in Examples 1-4 remained basically unchanged during the 18-hour test.
[0104] In Comparative Examples 2-4, the Co samples obtained by equal volume impregnation loading are unevenly dispersed and occupy the active sites on the surface of α-MnO2, which will reduce the performance and the catalytic effect will not be improved but will be reduced. Therefore, in the durability test, the degradation rate of chlorobenzene will decrease more than that of α-MnO2.
[0105] The conversion rate and CO2 yield of comparative examples 5-8 are significantly lower than those of the samples with rod-shaped α-MnO2 as the carrier, because the chlorobenzene conversion rate of the composite materials with spherical, flower-shaped, δ-MnO2 or γ-MnO2 as the carrier is less than 90% at 350°C, and the decrease in chlorobenzene degradation rate within 18 hours is more obvious, and the catalytic effect is not long-lasting.
[0106] (3) A certain mass of catalyst was subjected to anti-interference evaluation of chlorobenzene catalytic oxidation activity in a fixed bed reactor, and the anti-interference evaluation conditions were as follows:
[0107] The atmosphere conditions for the simulated catalytic oxidation of chlorobenzene are: 600ppm chlorobenzene, interfering gas (100ppm SO2 or 100ppm NO or 500ppm toluene), 10% O2, N2 balance gas, gas flow rate = 100mL / min, corresponding reaction space velocity WHSV = 30000mL / (g·h), temperature is 350℃, and time is 18h. The difference in chlorobenzene conversion rate at the beginning of the reaction and after 18 hours is used to obtain the results. Figure 4 .
[0108] according to Figure 4 It can be seen that SO2, NO and toluene in the actual industrial flue gas components have a significant effect on the activity of the α-MnO2 sample prepared in Comparative Example 1 in catalytic oxidation of chlorobenzene, and the anti-interference ability is weak. However, SO2, NO and toluene in the actual industrial flue gas components have a relatively small effect on the activity of the material prepared in Example 1 in catalytic oxidation of chlorobenzene, indicating that the anti-interference ability of the Co3O4@α-MnO2 material is improved.
[0109] And after material performance analysis and testing, it was found that the sample prepared in Example 2 after loading Co3O4 had the highest surface Mn 4+ Concentration, stronger reducing ability and higher surface active oxygen species content and mobility, so the redox ability is the strongest and the anti-interference performance is the best. The anti-interference ability of Examples 1, 3-4 to SO2, NO and toluene is enhanced because of the rod-shaped α-MnO2 loading. However, for Comparative Examples 2-8, due to the poor dispersibility of the sample Co3O4 or due to the change in morphology or material structure, the anti-interference ability to SO2, NO and toluene is worse than that of the original α-MnO2.
[0110] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing Co3O4@α-MnO2 material, characterized in that: The steps include: (1) KMnO4 and (NH4)2C2O4·H2O are added to water for ultrasonic dispersion, followed by hydrothermal reaction, and finally filtered, washed, dried, and calcined to obtain rod-shaped α-MnO2 material; (2) Rod-shaped α-MnO2 material, Co(NO3)2·6H2O and urea are placed in water, followed by hydrothermal reaction, and finally filtered, washed, dried and calcined to obtain Co3O4@α-MnO2 material.
2. The method for preparing the Co3O4@α-MnO2 material according to claim 1, characterized in that: The mass ratio or molar ratio of KMnO4 and (NH4)2C2O4·H2O is 2:
1.
3. The method for preparing the Co3O4@α-MnO2 material according to claim 1, characterized in that: In the step (1), the temperature of the hydrothermal reaction is 180° C. and the time is 24 hours.
4. The method for preparing the Co3O4@α-MnO2 material according to claim 1, characterized in that: In the step (1), the calcination atmosphere is air atmosphere, the calcination temperature is 400° C., and the calcination time is 4 hours.
5. The method for preparing the Co3O4@α-MnO2 material according to claim 1, characterized in that: The mass ratio of the rod-shaped α-MnO2 material to Co(NO3)2·6H2O is 1:0.025-0.5; the molar ratio of Co(NO3)2·6H2O to urea is 1:
10.
6. The method for preparing the Co3O4@α-MnO2 material according to claim 1, characterized in that: In the step (2), the temperature of the hydrothermal reaction is 120° C. and the time is 12 hours.
7. The method for preparing the Co3O4@α-MnO2 material according to claim 1, characterized in that: In the step (2), the calcination atmosphere is air atmosphere, the heating rate is 2°C / min, the calcination temperature is 400°C, and the calcination time is 4h.
8. The Co3O4@α-MnO2 material prepared by the method for preparing the Co3O4@α-MnO2 material according to any one of claims 1 to 7.
9. The Co3O4@α-MnO2 material according to claim 8, characterized in that: The Co3O4@α-MnO2 material is Co3O4 loaded on the surface of a rod-shaped α-MnO2 material.
10. Use of the Co3O4@α-MnO2 material as claimed in claim 8 in catalytic oxidation of chlorobenzene.
Citation Information
Patent Citations
Ozone oxidation catalyst protective agent for degrading organic wastewater
CN105772110A
Metal doped modified layered [delta]-MnO2, preparation and applications thereof
CN110102287A
Organochlorine compound removing catalyst and method
JP1999216362A